Consistency of performances in the Tkatchev release and re-grasp on high bar - Hiley, M. J.; Yeadon, M. R.; Buxton, E. (Sports Biomechanics, 2007)
The Tkatchev on the high bar is a release and re-grasp skill in which the gymnast rotates in a direction during flight opposite to that of the preceding swing. Since the release window is defined as the time during which the gymnast has appropriate linear and angular momentum to ensure the bar can be re-grasped, it was speculated that the release windows for this skill would be smaller than for dismounts that are less constrained. One senior male gymnast competing at national standard performed 60 Tkatchev trials. A four-segment planar simulation model of the gymnast and high bar was used to determine the release windows in 10 successful and 10 unsuccessful performances of the Tkatchev recorded using a Vicon motion analysis system. Model parameters were optimized to obtain a close match between simulations and recorded performances in terms of rotation angle (1°), bar displacements (0.01 m), and release velocities (1%). Each matched simulation was used to determine the time window around the actual point of release for which the model had appropriate release parameters to complete the Tkatchev successfully. The release windows for the successful trials were small compared with those of dismounts. The unsuccessful trials were associated with later release and later timing of the actions at the shoulders and hips.